Southern wall of the Garbhagriha of the Kaner-ki-Putli Temple - Temples of India Project Team (Jio Institute, 2024)
On the southern wall of the garbhagriha (sanctum sanctorum) of the Kaner-ki-Putli Temple, there is a male figure (on the left) with an intricate hairstyle, a lengthy beard, and a moustache. He wears a short dhoti (a loose piece of clothing to cover the lower half of the body) and is adorned with various pieces of jewellery. The figure is playing a small drum fastened with a belt that can be seen on his shoulder. Adjacent to him stands a bejeweled deity whose face and arms are damaged. Additionally, a bull is depicted at the bottom.